CRYPTOCURRENCY VOLATILITY AND ITS SPILLOVER EFFECTS ON ASEAN STOCK MARKETS - Komarudin, Komarudin; Magfiroh, Diana (Journal of Management Economic and Financial, 2024)
AbstractThe increasingly strong integration of global financial markets has increased the influence of cryptocurrency dynamics on the traditional financial system. The study analyzed the volatility of major cryptocurrencies—particularly Bitcoin and Ethereum—and their spillover effects on ASEAN stock markets, including Indonesia, Malaysia, Thailand, Singapore, and the Philippines. Using daily data for the period 2018–2024, this study applied the GARCH-BEKK multivariate model combined with the Diebold–Yilmaz spillover index to capture the transmission of volatility between markets. The results show that there is a significant two-way spillover effect between cryptocurrencies and ASEAN stock indices, with Bitcoin having a stronger influence than Ethereum. The intensity of volatility transmission is proven to be higher in periods of global economic uncertainty, such as the COVID-19 pandemic and the post-pandemic recovery phase. These findings confirm the growing linkage between digital assets and traditional equity markets in developing countries. The contribution of this research lies in the empirical evidence regarding the financial contingency channels between cryptocurrencies and the ASEAN capital market that are still rarely explored. From a practical perspective, the results of this study have implications for portfolio diversification, risk management strategies, and regulatory frameworks in the region. Policymakers and investors are advised to more closely monitor cryptocurrency developments as part of macroprudential surveillance and investment decision-making in ASEAN financial markets